Project Report on Optimal Transport for Secure Spread Spectrum Water making of Still Images - ANUSUYA P, APARNA P, ARUN U K, SANTOSH KUMAR S (2014)
INTERNAL GUIDE: Mrs. NOOPUR SHARMA, MVJCE CD ONLY
Keywords: Secure Spread Spectrum Water making of Still Images